2014
DOI: 10.4239/wjd.v5.i3.342
|View full text |Cite
|
Sign up to set email alerts
|

Clinical therapeutic strategies for early stage of diabetic kidney disease

Abstract: Diabetic kidney disease (DKD) is the most common cause of chronic kidney disease, leading to end-stage renal disease and cardiovascular disease. The overall number of patients with DKD will continue to increase in parallel with the increasing global pandemic of type 2 diabetes. Based on landmark clinical trials, DKD has become preventable by controlling conventional factors, including hyperglycemia and hypertension, with multifactorial therapy; however, the remaining risk of DKD progression is still high. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 132 publications
(133 reference statements)
4
36
0
3
Order By: Relevance
“…This seems to support the linear relation between vitamin D deficiency and progression of MAU reported in T2DM patients [13,27] , while also emphasizing the potential benefit of the normalization of vitamin D levels in the reduction of renal and cardiovascular risks associated with MAU in these patients [12,13] .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This seems to support the linear relation between vitamin D deficiency and progression of MAU reported in T2DM patients [13,27] , while also emphasizing the potential benefit of the normalization of vitamin D levels in the reduction of renal and cardiovascular risks associated with MAU in these patients [12,13] .…”
Section: Discussionsupporting
confidence: 53%
“…This seems notable, since MAU is considered to be a biomarker for diagnosing diabetic kidney disease, and is a predictive factor for the progression to end-stage renal disease (ESRD) and increased cardiovascular risk among diabetic patients [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Multifactorial management, including diet therapy and glycaemic, BP and lipid control, is recommended for diabetic nephropathy. Regarding diet therapy, the efficacy of a low-protein diet (LPD) for advanced diabetic nephropathy remains controversial [2]. Previous clinical studies have not consistently shown beneficial effects of an LPD for the preservation of renal function in diabetic nephropathy [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…1 Multifactorial management, including diet therapy and glycemic, blood pressure (BP), and lipid control, is recommended for diabetic nephropathy. 2 Some patients with advanced diabetic nephropathy rapidly progress to ESRD, despite having received adequate multifactorial treatment. Therefore, a novel and more beneficial treatment to suppress diabetic nephropathy has to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…2 Clinically, albuminuria is the hallmark biomarker for the diagnosis of diabetic nephropathy, and it is also used to stage diabetic nephropathy. The histopathological features of diabetic nephropathy in humans include glomerular hypertrophy, a thickening of the glomerular basement membrane, and mesangial matrix expansion, including the formation of glomerular nodular lesions known as Kimmelstiel-Wilson nodules.…”
Section: Introductionmentioning
confidence: 99%